Luminescence and physical properties of copper doped CdO derived nanostructures - Benhaliliba, M.; Benouis, C. E.; Tiburcio-Silver, A.; Yakuphanoğlu, Fahrettin; Avila-Garcia, A.; Tavira, A.; Mouffak, Z. (Elsevier Science Bv, 2012)
In this paper, we studied the photoluminescence (PL), the morphological, electrical and optical properties of pure and copper-doped cadmium oxide. CdO films were grown by a facile sal-gel spin coating process at 1200 rpm, and doped with copper at 2 and 3%. A (1 1 1)-oriented cubic structure with a lattice parameter of a=4.69 angstrom was confirmed by X-ray diffraction. Copper was shown to improve the optical transmittance in the short wavelength range of the visible spectrum. The optical band gap of CdO ranged between 2.49 and 2.62 eV as a result of Cu content. At room temperature, resistance fell drastically with Cu doping levels. AFM analysis of samples exhibited nano-mounts and nanowires. Finally, PL results showed a strong blue-violet emission peak at 2.80 eV. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: CdO thin films; Spin-coating; Sol-gel; Crystalline structure; Cu doping; Photoluminescence